Disturbance of Ecological Self and Impairment of Affordance Perception - Kim, Nam-Gyoon; Effken, Judith A. (Frontiers in Psychology, 2022)
The concept of affordance Gibson introduced is radical and controversial. Defined as the environmental properties taken with reference to an animal’s body and action capabilities, affordance conveys values and meanings the environment offers. Importantly, affordance is not just an important concept of a particular theory in psychology, but as the source of meanings and values, carries real psychological implications. Indeed, we contend that it is the psychological implications engendered by (absence of) affordances that underlie the conditions manifested by some mental patient populations. In particular, those mental disorders suspected to be caused by disturbance of “minimal selves” impair the perceptual capacity for affordances. As a result, the patients, deprived of values and meaning, are unable to relate with environmental elements in meaningful ways, and ultimately become experiencing their selves as detached from their bodies and from the world. We describe two studies conducted in our laboratory in which patients with schizophrenia and Alzheimer’s disease were shown to have impaired capacity to perceive affordances. We discuss the potential utility of clinical populations as a viable testing ground to assess the validity of affordance.